Social Practices and Dynamic Non-Humans Nature, Materials and Technologies - Maller, Cecily; Strengers, Yolande (Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
The robots are coming! So too is the 'age of automation', the march of 'invasive' species, more intense natural disasters, and a potential cataclysm of other unprecedented events and phenomena of which we do not yet know, and cannot predict. This book is concerned with how to account for these non-humans and their effects within theories of social practice. In particular, this provocative collection tackles contemporary debates about the roles, relations and agencies of constantly changing, disruptive, intelligent or otherwise 'dynamic' non-humans, such as weather, animals and automated devices. In doing so contributors challenge and take forward existing understandings of dynamic non-humans in theories of social practice by reconsidering their potential roles in everyday life. The book will benefit sociology, geography, science and technology studies, and human- (and animal-) computer interaction design scholars seeking to make sense of the complex entanglement of non-human phenomenaand things in the performance of social practices.